Pendampingan Pembelajaran Maharah Qira’ah Menggunakan Media Visual - Zainuri, Zainuri; Wahyudi, Imam (INAIFAS Press, 2023)
Reading activity is a communication process between readers and writers through reading texts. The aim of this community service activity is to apply a good method. I apply a qiroah method which is very practical and interesting in providing a complete, short, concise and simple understanding of learning.The use of learning media will depend on the learning method used by the teacher. The method used by the author is three strategies, namely: (1) preparation (2) implementation of activities (3) evaluation of activities. Community service activities in the form of assisting students in learning maharoh qiroah with visual media can be a solution to ignite the enthusiasm of students in learning Arabic. After mentoring, the assisted subject can read Arabic correctly.